Impact analysis of Farmer FIRST Programme in Haryana - Manjeet, Manjeet; Malik, Joginder Singh; Niwas, Ram; Kumar, Rupender (The Indian Journal of Agricultural Sciences, 2020)
The study was carried out to assess the impact of Farmer FISRT Programme on agricultural practices and economics in two purposively selected districts of Haryana namely Karnal and Hisar where Farmer FIRST programme was implemented by NDRI and CCSHAU respectively. In total 240 farmers, viz. 120 farmers from each district comprising 60 farmers each from adopted and non-adopted villages were selected at random as a beneficiary and non-beneficiary for present study. The study was conducted in 2018 and impacts of FFP were assessed using standard methodology. Results revealed that beneficiaries of FFP had high extension contact (41.67%), mass media exposure (25.00%), scientific orientation (72.50%), economic motivation (65.84%) and risk orientation (25.84%). The findings of the study revealed that there was a considerable difference between adopted and non-adopted villages about the concerning farmers’ adoption of recommended agricultural practices, viz. information of seed and variety, on water supply, fertilizer management, weed management, plant protection, information of marketing and the information of supporting factors. This showed the positive impact of FFP on agricultural practices and made a desirable outcome in the study. Based on the finding government should implement such programme on broad level to increase the interaction between farmer and scientist community.